SOME ENVIRONMENTAL PROBLEMS RISING FROM SHRIMP CULTURE ON SANDY COASTS IN NINH PHUOC, NINH THUAN PROVINCE - Ngoc, Phan Thi (Vietnam Journal of Marine Science and Technology, 2007)
Ninh Thuan is a coastal area which has potentials for aquaculture development in sandy Coast. It used to be in first position of shrimp culture on sandy coasts and in extending culture area. The sandy coasts are shared resources of different economic activities and play an important role in regulating and keeping the scarced groundwater resources in a waste land where the sunligh more than the rain. So that, the sandy coasts are very sensitive and vulnerable and should pay an attention in exploitation and utilization. The shirmp culture on sandy coasts in Ninh Phuoc have already got primary econimically bennifits, but unstable due to causing a lot of environmental problems and negative impacts such as: pollution whithin and around the aquaculture areas; decline quality and quantity of the groundwater; caused pollution of nearshore environment; decrease coastal protective forest area and increase wasteland areasl, ... Especially, the environmental problems have impacted to economy, to liveliehoods and daily activities of local people. This article presents the studied results in Ninh Phuoc district and recomended solutions for coastal sands sustainable development in Ninh Thuan in particular and for sandy sustainable shrimp culture in Vietnam in general.